Influência do fermento natural sobre as características microbiológicas, físico-químicas e perfil de textura do queijo minas artesanal da região Campo das Vertentes - Carolina Campos Cabrini (2017)
The natural yeast traditionally known as "pingo" is widely used in the manufacture of artisanal Minas cheeses. It is also given the role of one of the main agents that confers identity to cheeses. This premise implies that without the natural starter there would be less diversity of cheeses from the regions and before this the use of natural yeast became obligatory for the Minas artisanal cheese. However, it is necessary to scientifically test this premise to prove the need to use this yeast and to support the current legislation. The objective of this work was toinvestigate the effect of the addition of natural starter on the microbiological, physico-chemical and texture characteristics of the artisanal Minas Gerais cheese from the Campo das Vertentes region. For this, a bibliographical review was made to search in the scientific literature for studies related to the aforementioned objective. From a contrary perspective, studies show the existence of pathogens and alterers in this yeast which opens the possibility for the same tocompromise the quality of the cheeses. For the experiment, samples of natural yeast from different properties of the region were collected and taken to produce the cheeses with and without the yeast. The analyzes were performed at the times: 7, 14, 21, 28 and 35 days, withthree replicates. The results showed that the yeast exerted some inhibitory effect on microbial groups of artisanal Minas Gerais cheeses. However this difference does not determine positive or negative action for the cheeses. Continuity of studies is necessary given the mandatory useof yeast and under the conditions studied the need for its use has not been verified.